(untitled) (Journal of Oriental Studies, 2019)
In this article is considered life and works of the Second Teacher Abu Nasr alFarabi referring to historical data in the Arab sources and the huge contribution of the scientist in a medieval ArabMuslim civilization reveals. Written monuments of Abu Nasr alFarabi and the invaluable information about ancient Otyrar (Farab) reached us through bibliographic and encyclopedic works of medieval Arabicspeaking historians chroniclers are considered important sources for modern to a farabi’s studies. The role and importance of the state program which are carried out at the initiative of the First President of Kazakhstan “Cultural heritage”, “The people – in a history stream”, “Seven sides of the Great steppe” in return of the richest written monuments Abu Nasr alFarabi to the Homeland – Kazakhstan are defined. Key words: Heritage alFarabi, medieval science and culture, sources, farabi’s studies, bibliographic indexes.